The Use of Instagram and Facebook as Marketing Platforms for Hampers Reseller Products: A Case Study of Nings Kios - Muh Riswandi Palawa; Andi Indriani Ibrahim; Christin Aprilia Kaleka; Siti Aisyah; Dwi Apriliani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The development of digital technology has opened new opportunities in the world of entrepreneurship, particularly through the use of social media. This study aims to examine how Instagram and Facebook are utilized as sales platforms for hampers by Nings Kios, a reseller business based in Palu City. This research employs a qualitative method with a case study approach. Data was collected through in-depth interviews, observation, and documentation of the business owner. The findings indicate that Nings Kios uses Instagram and Facebook as primary tools for product promotion, building customer relationships, and effectively expanding market reach. Features such as Instagram Stories, Feed, and Facebook posts are leveraged to enhance product appeal and streamline interaction and transaction processes. This demonstrates that the strategic use of social media can increase audience reach and sales, even when managed by a single individual with limited resources. This study provides a real-world illustration of how small business owners in urban areas like Palu City can utilize social media as an effective entrepreneurial tool.